Responses of macrophages to the danger signals released from necrotic cells. (5th August 2014) - Kimura, Toshifumi; Kobayashi, Shuhei; Hanihara-Tatsuzawa, Fumito; Sayama, Aoi; MaruYama, Takashi; Muta, Tatsushi
Abstract : UDP is a danger signal from necrotic cells that induces MCP-3 in macrophages Abstract: The immune system maintains homeostasis by recognizing and responding to cell death caused by various stresses. The immune response is considered to be elicited by 'danger signals' released from necrotic cells. However, the identity of the danger signals remains elusive. In this study, we focused on the expression of chemokines by macrophages stimulated with necrotic cells. In mouse bone-marrow-derived macrophages, the chemokine monocyte chemoattractant protein (MCP)-3 was induced at both the mRNA and protein levels in response to heat-killed murine cells. The induction of MCP-3 was also observed in MyD88-deficient macrophages, indicating that Toll-like receptors and the IL-1 receptor are not involved in this response. Consistent with this observation, the activation of NF-κB was not detected in RAW264.7 macrophages stimulated with necrotic cells. Treatments with proteinase K, DNase I or RNase A did not affect the 'stimulating activity' of necrotic cells. In contrast, treatment with apyrase, which removes phosphates from nucleoside tri- and di-phosphates, abolished the inducing activity. Purified UDP at 30 µM concentration elicited similar induction of MCP-3 in RAW264.7 macrophages. Small interfering RNA-mediated knock-down of the UDP receptor P2Y6 in RAW264.7 cells significantly reduced the induction of MCP-3 in response to necrotic cells, but not its induction by lipopolysaccharide. Furthermore, ectopic expression of the P2Y6 receptor in HEK293 cells conferred responsiveness to necrotic cells. These results suggest that UDP released by necrotic cells plays a critical role as an endogenous danger signal and that P2Y6 is required for the induction of MCP-3 in response to necrotic cells.